2012
DOI: 10.1111/j.1751-2980.2012.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Once‐daily versus multiple‐daily mesalamine for patients with ulcerative colitis: A meta‐analysis

Abstract: OBJECTIVE:To systematically review the efficacy and safety of once-daily (OD) mesalamine for the treatment of ulcerative colitis (UC) compared with multiple-daily (MD) mesalamine. METHODS:Electronic databases up to July 2011 were searched for related studies evaluating the efficacy of OD vs MD for treatment of UC. Only randomized controlled trials (RCTs) were considered eligible. Remission rates or relapse rates were analyzed using intention-to-treat (ITT) and per-protocol (PP) analysis. Pooled relative risk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…A similar study with once daily and three times daily dosing of mesalazine also showed no difference in incidence of adverse events . Several other studies have similarly demonstrated no difference in adverse events between once daily compared to divided dosing for mesalazine …”
Section: Resultsmentioning
confidence: 71%
“…A similar study with once daily and three times daily dosing of mesalazine also showed no difference in incidence of adverse events . Several other studies have similarly demonstrated no difference in adverse events between once daily compared to divided dosing for mesalazine …”
Section: Resultsmentioning
confidence: 71%
“…However, slow release of the active ingredient constitutes a more elegant and patient‐friendly option. It has also been shown that split dosing of oral 5‐ASA can be replaced by once daily administration …”
Section: Modifications That Have Recently Been Made To Existing Theramentioning
confidence: 99%
“…It has also been shown that split dosing of oral 5-ASA can be replaced by once daily administration. 11 A new MMX delivery system of 1.2 g of MMX mesalazine was tested in a preliminary trial in UC and showed similar rates of remission induction to the combination of mesalazine enema and oral placebo in patients with left-sided colitis. 12 In two pivotal trials with MMX mesalazine at higher doses 13,14 patients with active UC were randomized to receive 2.4 g or 4.8 g of MMX mesalazine once daily versus placebo or 800 mg of slow-release mesalazine.…”
Section: Novel Delivery Mode Of 5-asa: Multi-matrix (Mmx) Mesalazinementioning
confidence: 99%
“…Several previous systematic reviews and meta‐analyses have compared OD with MD dosing of oral mesalamine . To our knowledge, however, no previous meta‐analysis has studied the administration of mesalamine suppositories and the present study is the first to include trials comparing OD with MD suppositories.…”
Section: Discussionmentioning
confidence: 95%
“…Zhu et al [30] showed that OD dosing can achieve higher remission rates not only for inducing but also for maintaining remission. Tong et al [32] stated that OD mesalamine can achieve a better efficacy than MD dosing in inducing remission than in maintaining remission (RR 0.80, 95% CI 0.64-0.99). As is well known several factors [34] influence drug efficacy including total doses, formulation of the drug, different routes of administration, disease course and duration of therapy.…”
Section: Discussionmentioning
confidence: 99%